Stress neuropeptide levels in adults with chest pain due to coronary artery disease: potential implications for clinical assessment - Anastasiou-Nana, M.; Kletsiou, Eleni; Giannakopoulou, Margarita; Bozas, Evangelos; Iliodromitis, Efstathios K.; Papathanassoglou, Elizabeth (My University, 2010)
: Substance P (SP) and neuropeptide Y (NPY) are neuropeptides involved in nociception. The study of biochemical markers of pain in communicating critically ill coronary patients may provide insight for pain assessment and management in critical care. Purpose of the study was to to explore potential associations between plasma neuropeptide levels and reported pain intensity in coronary critical care adults, in order to test the reliability of SP measurements for objective pain assessment in critical care.
Keywords: Cardiovascular System; Cardiology